The “obese liver” and gastrointestinal cancer risk - Lonardo, Amedeo; Roncucci, Luca (Translational Gastroenterology and Hepatology, 2020)
From an evolutionary point of view the accumulation of nutrients under the form of fatty substrates offers a protection during periods of famine (1). While the adipose tissue is the physiological reservoir of energetic fatty substrates, the liver is not (2). The normal liver is indeed virtually devoid of any fat content (3).